Dynamics of the results of the correction a training process in skilled female kayak rowers - Чеханюк [Olga Chehanyuk] Ольга Петрівна (Slobozhanskyi Herald of Science and Sport, 2013)
<!–[if gte mso 9]> Normal 0 false false false RU X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–> This article presents the results of pedagogical experiment of correction the training process of qualified female kayak rowers considering their future specialization. The research involved 16 athletes (eqsperimental group – 8, the control group – 8 athletes)with training qualification Master of Sport and Candidate of Master of Sport . During the pedagogical experiment in both groups of athletes have been occurred positive changes in all studied norms of physical fitness. But not all the results have statistical reliability of differences and different growth rates. Athletes have improved their top quality vastly. For athletes, specializing on the distance of 200 meters, significantly improved following qualities: strength endurance, maximal strength, speed endurance and speed. <!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–><!–[if gte mso 10]> <![endif]–>